Analisis Strategi Pemasaran Politik Kampanye Kukuh Haryanto Sebagai Calon Legislatif DPRD Kabupaten Wonogiri Dalam Kontestasi Pemilihan Umum Tahun 2024 - Ardana, Shildamullah Danendra Mukti; Purwaningsih, Titin (Universitas Tribhuwana Tungga Dewi, 2024)
The 2024 general election stands out as one of the most dynamic elections compared to previous ones. This election was marked not only by the drama surrounding presidential and vice-presidential candidates but also by political maneuvers and the creative campaign strategies of legislative candidates from various political parties. Kukuh Haryanto, a street artist known as a street musician or